Bersandar Kapas, Berujung Bencana: Perspektif Ekonomi Politik dalam Sejarah Perdagangan Kapas di Flores, 1912-1943 - Martin Elvanyus De Porres (Umbara, 2021)
This study discusses the historical process of cotton introduction and commercialization in Maumere, Sikka Regency, Flores, East Nusa Tenggara, from 1912 to 1943 using political economy perspective. In the early 20th century, the Netherlands enacted the 1870 Agrarian Law. Flores was one of the areas officially colonized by the Dutch. A number of crop commodities were introduced, including the establishment of plantations, to participate in global trade traffic. Cotton is one of the plants introduced to Flores for the benefit of the world’s textile industry. The people of Flores were forced to plant, but along the way, the plants did not succeed in providing surplus value to trading companies, let alone to local people. This study was conducted based on literature. This study finds that the power relations between the Dutch East Indies government, trading companies, and local rulers, led to the forced commercialization. This interwoven political economy relationship had an impact on the existence of a primitive and capital accumulation mechanism. The mechanism causes local residents to lose land and shelter and some of them fall into forced labor to serve the feudal elite and colonial rulers.